Perceived compliance and barriers to care in sublingual immunotherapy. Issue 5 (9th February 2017) - Kumar, Manvinder S.; Oh, Melissa S.; Leader, Brittany; Rotella, Melissa; Stillman, Leisa; DelGaudio, John M.; Wise, Sarah K.
Abstract : Background: For allergy immunotherapy to be effective, patient compliance is critical. However, aqueous sublingual immunotherapy (SLIT) may be considered demanding for patients, requiring strict daily dosing and refilling of medication at regular intervals. In this study we sought to determine how patients perceive their own compliance with SLIT and identify barriers that may hinder compliance. Methods: Using a retrospective review, 46 patients currently undergoing aqueous SLIT were identified to have less‐than‐excellent compliance based on frequency of clinic visits for SLIT refills. Twenty‐eight of these patients completed a phone survey regarding symptom improvement, compliance, and barriers to care. In addition, 56 patients who withdrew from therapy before completion were polled about barriers to adherence. Results: Of the 28 patients participating in the initial phone survey, 24 (86%) reported subjective improvement in symptoms on SLIT, despite less‐than‐excellent compliance. Nineteen (68%) of these patients perceived their own compliance to be excellent. Eighteen patients (65%) reported the inconvenience of scheduling and attending clinic appointments to be the main reason for noncompliance. The most common reasons for withdrawal from therapy were cost (27%), lack of effectiveness (25%), and difficulty with compliance (14%). Conclusion: The majority of aqueous SLIT patients perceived their compliance to be excellent, although, based on a previous study, these patients did not reach excellent compliance benchmarks. Inconvenience of clinic visits and cost of therapy were found to be the most common barriers to care. Despite what providers perceived as less‐than‐excellent compliance, 82% of patients reported symptom improvement with SLIT.